The Impact of 3:1 Ketogenic Diet on Cardiac Repolarization Changes in Children with Refractory Seizures: A Prospective Follow-Up Study - Özdemir, Rahmi; Güzel, Orkide; Küçük, Mehmet; Karadeniz, Cem; Yılmaz, Ünsal; Calik, Tansel; Meşe, Timur (Neuropediatrics, 2016)
Background The association between ketogenic diet (KD) and prolonged QT interval, life-threatening ventricular arrhythmias, and sudden death is controversial.Aim We aimed to prospectively evaluate the effect of KD on electrocardiography (ECG) measures in children with refractory epilepsy.Method A total of 70 children with drug-resistant epilepsy who received a KD for at least 12 months were included in the study. The standard 12-lead electrocardiography was performed in all patients before the beginning and in the 12th month of KD. Heart rate, P-wave duration and dispersion, corrected QT interval and QT dispersion, and Tp-e interval were measured.Results All ECG-derived parameters, but P-wave dispersion increased after 12 months of KD compared with the baseline values. However, these changes were not statistically significant.Conclusion A 12-month long 3:1 KD treatment exerts no deleterious effect on cardiac repolarization measures.
Keywords: ketogenic diet; children; electrocardiography; cardiac repolarization; T peak–T end interval